2012 IEEE Symposium on Business, Engineering and Industrial Applications 2012
DOI: 10.1109/isbeia.2012.6422872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICT on society — Higher education students in South-East Asia

Abstract: The integration of Information & Communication Technologies (ICT) and Education has been considered the main key to human progress. The aim of ICT is to transfer advances in sciences and technology for the socio-economic development, industrialization and modernization of the country to promote international co-operation in ICT to bring into a country the latest achievements of the world's science and technology. Education institutions are a vehicle to produce skilled professionals, to close the gap between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…No significant difference was revealed among the two groups. A study was carried out by Veerasamy and de Souza-Daw (2012) which was based on examining the educational circumstances in South-Asian countries; specifically, India, Vietnam and Papua New Guinea. An analysis was performed on the students of higher education with respect to the usage of ICT and its impact on teachers’ and students’ performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…No significant difference was revealed among the two groups. A study was carried out by Veerasamy and de Souza-Daw (2012) which was based on examining the educational circumstances in South-Asian countries; specifically, India, Vietnam and Papua New Guinea. An analysis was performed on the students of higher education with respect to the usage of ICT and its impact on teachers’ and students’ performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…One of the areas that ICT had impacted most is the education sector. It participated and facilitated the progress of education, industrialization, socio-economic development, and modernizations of the country (Ashok and Tony, 2012). Today's students have more chance to access and reach knowledge easily and quickly than their predecessors 30 years ago.…”
Section: Wwwkesitakademicommentioning
confidence: 99%
“…In countries such as Slovakia, it was noted that educational institutions utilizing ICT in learning produced better student results than those institutions where ICT utilization was not yet realized (Pal'ova, 2011). Studies conducted in three South-East Asian countries, that is, India, Vietnam, and Papua New Guinea, also revealed that ICT provides learners with learning techniques that could help them to supplement their current knowledge and hence to attain more knowledge and better marks (Srivastava, 2012;Veerasamy & de Souza-Daw, 2012). According to Ashiono, Mwoma, and Murungi ( 2018) the use of ICT in learning increases opportunities for underperforming learners to actively participate in learnings, hence, improving their academic performance as learning is found to be attractive, easy, and enjoyable.…”
Section: Introductionmentioning
confidence: 99%